MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DI KELAS MELALUI REWARD AND PUNISHMENT DI SDN 41/IX DESA MUARO JAMBI KECAMATAN MARO SEBO KABUPATEN MUARO JAMBI - Siti Rohani (Indonesian Publication Center, 2020)
The background of the holding of this school action research is the lack of discipline of teachers in teaching in the classroom. The purpose of this study was to improve teacher discipline in teaching attendance in class through reward and punishment at SDN 41 / IX, Muaro Jambi Village, Maro Sebo District, Muaro Jambi Regency. The subjects of this school action research were teachers at SDN 41 / IX, Muaro Jambi Village, Maro Sebo District, Muaro Jambi Regency. In this School Action Research (PTS), action was tried in the form of the application of Reward and Punishment for teachers at SDN 41 / IX, Muaro Jambi Village, Maro Sebo District, Muaro Jambi Regency. This research was conducted in two cycles. The results of the research in cycle 1 the discipline of teacher attendance in class less than 10 minutes late reached 28% so that it did not meet the predetermined indicators of 75%. In the second cycle the discipline of teacher attendance in teaching in the classroom less than 10 minutes late reached 86% results, from the results of research and data analysis, in the second cycle, the discipline of teacher attendance in class in the learning process increased and met the predetermined indicators of 75%. It can be concluded that to improve the discipline of teacher attendance in the classroom in learning activities, it can be done by applying Reward and Punishment to the teacher.